2010
DOI: 10.1002/eji.201040558
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells exhibit enhanced migratory characteristics, a feature impaired in patients with multiple sclerosis

Abstract: Migration of immune cells characterizes inflammation and plays a key role in autoimmune diseases such as MS. CD41 Foxp31 regulatory T cells (Treg) have the potential to dampen immune responses but show functional impairment in patients with MS. We here show that murine Treg exhibit higher constitutive cell motility in horizontal migration on laminin, surpass non-Treg in transwell assays through microporous membranes as well as across primary brain endothelium and are present in the naïve CNS to a significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 30 publications
3
50
0
4
Order By: Relevance
“…8 We recently showed that natural Tregs bear an intrinsic propensity for migration, thus increasing the probability of a Treg-endothelial cell interaction compared with non-Tregs. 34 In the present study, we extended these findings by demonstrating that Tregs are especially prone to adhere to the vascular endothelium via LFA-1/ICAM-1 binding under ischemic conditions, and blocking of this pathway abolished the stroke-enhancing activity of Tregs by reducing intravascular thrombosis and improving tissue reperfusion. Moreover, depletion of platelets also prevented Tregdriven infarct progression in Rag1 Ϫ/Ϫ mice.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…8 We recently showed that natural Tregs bear an intrinsic propensity for migration, thus increasing the probability of a Treg-endothelial cell interaction compared with non-Tregs. 34 In the present study, we extended these findings by demonstrating that Tregs are especially prone to adhere to the vascular endothelium via LFA-1/ICAM-1 binding under ischemic conditions, and blocking of this pathway abolished the stroke-enhancing activity of Tregs by reducing intravascular thrombosis and improving tissue reperfusion. Moreover, depletion of platelets also prevented Tregdriven infarct progression in Rag1 Ϫ/Ϫ mice.…”
supporting
confidence: 59%
“…Indeed, circulating natural CD4 ϩ CD25 ϩ Tregs expressed significantly higher amounts of LFA-1 than CD4 ϩ CD25 Ϫ non-Tregs on day 1 after tMCAO (n ϭ 6, P Ͻ .05; Figure 6A right), which confirms our previous data under nonischemic conditions. 34 Mechanistically, blocking of LFA-1 in CD4 ϩ CD25 ϩ -reconstituted Rag1 Ϫ/Ϫ mice Rag1 Ϫ/Ϫ mice were treated with antiplatelet serum to deplete circulating platelets or controls serum and infarct volumes were determined on day 1. Depletion of platelets reversed the stroke-enhancing effect of CD4 ϩ CD25 ϩ Tregs and also of CD4 ϩ CD25 Ϫ non-Tregs in Rag1 Ϫ/Ϫ mice.…”
Section: Regulatory T Cells Promote Stroke 685mentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease or functional abnormality in Tregs can result in various autoimmune diseases. [9][10][11] Regarding heart failure, Tang, et al reported an association between peripheral Tregs and heart failure in HF patients who were stable on optimal therapy for at least 3 months.…”
Section: Cd4mentioning
confidence: 99%
“…For flow cytometric analysis of immune cell infiltration in the CNS, mononuclear cells were isolated as previously described (48). Briefly, anesthetized mice were transcardially perfused with 20 mL of PBS, and CNS tissue was removed, homogenized with scissors, and digested with Collagenase Type IA (0.4 mg/mL; Sigma Aldrich) for 30 min in a water bath at 37°C.…”
Section: Methodsmentioning
confidence: 99%